2018
DOI: 10.1002/erv.2628
|View full text |Cite
|
Sign up to set email alerts
|

The Adult Eating Behaviour Questionnaire in a bariatric surgery‐seeking sample: Factor structure, convergent validity, and associations with BMI

Abstract: The aim of this study was to validate the Adult Eating Behaviour Questionnaire (AEBQ), a measure of food approach and avoidant traits, for use in bariatric surgery candidates. Participants were 337 bariatric surgery candidates in the Mid-Atlantic United States. Confirmatory factor analysis suggested that one item did not load onto its original factor. A 34-item, eight-factor model had better fit than a seven-factor model; dropping the Hunger factor, as previously suggested, did not improve fit. The factors had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 29 publications
15
26
1
1
Order By: Relevance
“…Hunot-Alexander et al [ 12 ] also presented similar observations associated with correlations between appetitive traits assessed by the AEBQ, as well as differences between female and male respondents, and in this study, all of the food approach subscales were positively inter-correlated. In the study of Zickgraf and Rigby [ 16 ], no significant sex-dependent differences were observed for other subscales. However, it is not surprising that observations are inconsistent, as the abovementioned study of Zickgraf and Rigby [ 16 ] was conducted in a mixed sample of adolescents and adults, who were defined as patients pursuing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hunot-Alexander et al [ 12 ] also presented similar observations associated with correlations between appetitive traits assessed by the AEBQ, as well as differences between female and male respondents, and in this study, all of the food approach subscales were positively inter-correlated. In the study of Zickgraf and Rigby [ 16 ], no significant sex-dependent differences were observed for other subscales. However, it is not surprising that observations are inconsistent, as the abovementioned study of Zickgraf and Rigby [ 16 ] was conducted in a mixed sample of adolescents and adults, who were defined as patients pursuing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Zickgraf and Rigby [ 16 ], no significant sex-dependent differences were observed for other subscales. However, it is not surprising that observations are inconsistent, as the abovementioned study of Zickgraf and Rigby [ 16 ] was conducted in a mixed sample of adolescents and adults, who were defined as patients pursuing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the Chinese version of the AEBQ (He, Sun, et al, ) was used. Previous studies indicate that the both the English and Chinese versions of the AEBQ are psychometrically sound (He, Sun, et al, ; Hunot et al, ; Mallan et al, ; Zickgraf & Rigby, ). Consistent with prior research (Ellis, Galloway, et al, ; Tharner et al, ), the following subscales were used: Food Responsiveness, Enjoyment of Food, Satiety Responsiveness, Food Fussiness, and Slowness in Eating.…”
Section: Methodsmentioning
confidence: 99%
“…“Picky” eating (PE) is characterized by avoidance of foods due to aversions to their sensory properties, including new foods (food neophobia), foods that are familiar but nonpreferred, and preferred foods based on seemingly minor variations in their preparation and/or presentation (Dovey, Staples, Gibson, & Halford, ; Taylor, Northstone, Wernimont, & Emmett, ; Wildes, Zucker, & Marcus, ; Zickgraf & Schepps, ). PE is associated with reduced dietary variety, and in extreme cases, imbalanced or inadequate diets (e.g., Kauer, Pelchat, Rozin, & Zickgraf, ; Zickgraf & Rigby, ). Picky eating behaviors, varying from mild to severe, are common across the lifespan.…”
Section: Introductionmentioning
confidence: 99%